“Empresta, por favor”?: processos de ensinar e de aprender em brincadeiras de crianças na educação infantil - Nicolielo, Maria Elisa (2015)
Before the great influence that the playfu has in the childhood by providing children to create, to experience new situations, to connect with their peers and to experience elements of culture, it was taken as na ally in education, especially in Young children education as part of many school practices. Thus, this work aimed to know and understand the processes of teaching and learning that occur in the relationships between children and between them and the teacher in the context of play in early childhood education. It also sought to identify how the toy is placed by the children at that time of the play and what roles are as signed by them to that object. We began conducting a literature search in databases and to support us about it, we conducted a theoretical research around topics such as childhood, children, early childhood education in Brazil and playfulness. Qualitative, the research took place with a group of 14 children, having a mean age of 3 years, enrolled in ‘Maternal II’ and their teacher at a public school in kindergarten in the city of Pederneiras - SP. With the approach of conducting research with children, the researcher conducted participant observation, tracking the moment of play that occurred on Fridays, the day the children took his toys to school. Recording the data collection field diaries used and performed the analysis with reference to the content analysis. At the end of the Field research 13 daily were written, one for each insert performed. The authors Who guided the data discussion were: Brougère, Borba, Corsaro, Freire, Rossetti-Ferreira, Sommerhalder; Alves, Carvalho, Kishimoto, Guimarães; Barbosa, Horn, Leontiev and others. The results show that in play children experienced processes of teaching and learning to strengthen the group interaction: knowing how to live and play with each other, lending, trading, deny the request to someone, teach new ways to play, meet other spaces, strengthen friendly relations. When interacting with the toys, children have shown that these objects were essential to their play, being used the way they are or processed according to the imagination or need for the play could occur. When they experience such processes of teaching and learning these children have shown that in the free play, they lived training experiences for life.